Comparison of Antibody Titre Against Salmonella Species among Healthy Individuals and Febrile Patients - Barakoti, Achut; Rai, Junu Richhinbung; Adhikari, Ram Prasad; Khanal, Laxmi Kant (Journal of College of Medical Sciences-Nepal, 2018)
Background: Widal tube agglutination test is a widely used laboratory test for diagnosis of enteric fever especially in resource limited countries where blood culture are not routinely available. We studied the titres from different groups including febrile and healthy populations in order to identify the significant agglutination titre. Materials and Methods: This was a hospital based cross-sectional study. Subjects were divided into three groups: 1) 60 healthy blood samples from volunteer students, 2) 60 febrile non-typhoidal cases and 3) 58 culture positive patient for enteric fever. Results: Among 60 apparently healthy volunteers, agglutination of ≥ 1:20 for anti O and anti-H titres against serotype Typhi were seen in 40 and 46 samples respectively. A significant proportion of sample had a titre of ≥1:80 (n=19) and 1:160 (n=14) for anti O and anti-H titres against serotype Typhi respectively among healthy individuals. Similar observations were seen in febrile non typhoidal cases except for one which had a titre of ≥1:320 for anti O and anti-H titres against serotype Typhi. In blood culture positive typhoid cases, 56 samples showed agglutinations of ≥1:80 for both anti O and anti-H titres against serotype Typhi. However two of the total sample tested showed no agglutinations. In all cases from three groups, anti-H titre for S. enterica serotype Paratyphi A and B were below 1:80. Conclusions: Widal test can be used as presumptive diagnostic tool in all the suspected cases of enteric fever if the titres are specifically raised. Keywords: enteric fever; titre; widal aggultination test.